Poemat Maryjny Michała Antoniego Hackiego - Łukaszewicz-Chantry, Maria (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
The poem of the Abbot of Oliwa Michał Hacki can be considered as a poetic Mariological treatise which emphasises the privilege of the Immaculate Conception, questioned by the Reformation. Hacki gives numerous metaphors and titles of Mary, systematises them, classifies them into thematic groups and explains their meaning. By doing so, he preserves the hierarchy of theological truths and Christocentrism.